PRINCIPLE OF PURE UNIVERSALITY IN INTERNATIONAL BANKRUPTCY - Radović, Vuk (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
In this article the author analizes the principle of pure universality in international bankruptcy law. This is one of the most important theories in the field of cross-border insolvency, that came up as an answer to the dominance of principle of territoriality in nacional bankruptcy laws. In the first part of the article, the author determines the meaning and basic characteristics of the principle of pure universality. Afterwards, the most important advantages of this principle have been elaborated. They are supposed to be the justification for its introduction. Next part of the article points out to the most significant limitations of this principle, because potencial implementation must bear them in mind. In the last part of this article the author defines the basic conditions for the application of principle of pure universality. The author of this article argumented in favour of this principle, in spite of current domination of other theories.
Keywords: lex fori concursus; international bankruptcy; pure universality; principle of territoriality; principle of universality